Association between Pneumonia Development and Virulence Gene Expression in Carbapenem-Resistant Acinetobacter baumannii Isolated from Clinical Specimens - Ji Yun Bae; Ina Yun; Kang Il Jun; Chung-Jong Kim; Miae Lee; Hee Jung Choi (Canadian Journal of Infectious Diseases and Medical Microbiology)
We investigated the virulence gene expression of carbapenem-resistant Acinetobacter baumanii (CRAB) isolated from the respiratory samples of patients with CRAB pneumonia and those with CRAB colonization to identify the virulence genes contributing to CRAB pneumonia’s development and mortality. Patients with CRAB identified from respiratory specimens were screened at a tertiary university hospital between January 2018 and January 2019. Patients were classified into CRAB pneumonia or CRAB colonization groups according to predefined clinical criteria. A. baumannii isolated from respiratory specimens was examined for the expression levels of ompA, uspA, hfq, hisF, feoA, and bfnL by quantitative reverse-transcription polymerase chain reaction. Among 156 patients with CRAB from respiratory specimens, 17 and 24 met the criteria for inclusion in the pneumonia and colonization groups, respectively. The expression level of ompA was significantly higher in the pneumonia group than in the colonization group (1.45 vs. 0.63, P=0.03). The expression levels of ompA (1.97 vs. 0.86, P=0.02), hisF (1.06 vs. 0.10, P<0.01), uspA (1.62 vs. 1.01, P<0.01), and bfnL (3.14 vs. 2.14, P=0.03) were significantly higher in patients with 30-day mortality than in the surviving patients. Elevated expression of hisF (adjusted odds ratio = 5.93, P=0.03) and uspA (adjusted odds ratio = 7.36, P=0.02) were associated with 30-day mortality after adjusting for age and the Charlson score. uspA and hisF may serve as putative targets for novel therapeutic strategies.